Avendersteen in the Netherlands (Bulletin KNOB, 2009)
Between the 15th and 19th centuries Avendersteen (Avesnes stone) was used for many sculptural works in the Netherlands. The stone, locally used as building material, was excavated in underground quarries near the village of Avesnes-le-Sec, in the north of France. That region was part of the Netherlands in the 15th and 16th centuries. Avendersteen was transported along the river Scheldt. That is why most of the Avendersteen can be found in the southern part of the Netherlands, but it appears that it was also used in Utrecht and even in Kampen. The use of Avendersteen seems to be connected with sculptors from the Southern Netherlands, e.g. Colijn de Nole from Cambrai. Avendersteen is a very pure, finegrained Cretaceous limestone. Until recently the stone was not recognized by stone-experts and in many cases wrongly identified as Baumbergersteen (Baumberg stone), a calcareous sandstone from the surroundings of Münster in Germany. Avendersteen has a typical texture caused by burrowing organisms, a feature that is not found in Baumbergersteen.The findings indicate that Avendersteen was a very important material for sculpture between 1500 and 1900. However, nowadays only a few examples can be found, as Avendersteen easily weathers. Treatment of the stone has been applied to prevent weathering. These treatments need to be looked after, as they might even enhance the process of weathering.Avendersteen is the mason’s term for a white to light-grey limestone from Cretaceous North France, used in the Netherlands from the 15th century to approximately 1900. The stone was mined in underground quarries in the surroundings of the village of Avesnes-le-Sec, twelve kilometres north-east of Cambrai. Similar types of stone are known from nearby Hordain (Hordain stone). By way of the river Scheldt this limestone was transported downstream and traded in Antwerp. The greater part of the presently known monuments with sculpture made of Avendersteen are in Belgium and the Southern Netherlands, particularly in Breda and ‘s Hertogenbosch, but the material was also used in Utrecht, Amsterdam and Kampen. Almost without exception stonemasons and sculptors from the Southern Netherlands were involved in the application of Avendersteen.For a long time Avendersteen was mainly used for very finely detailed work. Around 1500 Avendersteen was delivered at various building sites (among others, the cathedral in Utrecht (the Dom) and St John’s Cathedral in ’s Hertogenbosch). In mineral contents and structure the limestone from Avesnes shows some similarity to Baumbergersteen, a calcareous sandstone from the surroundings of Münster. As Avendersteen has frequently been mistaken for Baumbergersteen, the use of Avendersteen for sculpture is much larger than was assumed so far. Although the ‘peak’ in its use was in the 16th and 17th centuries, this material continued to be used until well into the 19th century. The fact that the stone passed into disuse is to be explained by the availability of the white French limestone towards the end of the 19th century. However, Avendersteen is not the only type of stone that passed into disuse for this reason. The difficult mining of Gobertange stone to the east of Brussels was stopped for similar reasons.Nowadays the stone can still be obtained on a limites scale. A special 19th-century application are the three statues by the Antwerp sculptor J. de Cuyper at the façade of the Roman-Catholic church in Westwoud, in the northern part of North Holland.The material proved to be less suitable for external use, but in a number of cases it has nevertheless survived for a long time. Possibly this has to do with the treatment the stone was once subjected to. Research of the statues in Westwoud, which we hope will soon be restored, may result in new facts on the means used to protect the stone against every kind of weather. Research, including determination of the materials used, is important for a correct diagnosis and possible intervention. However, for most objects from Avendersteen it is already too late. In Vught the stone is fully saturated with acrylic resin and this seems to be the reason why the material can be preserved in situ. This intervention is irreversible.The ornamental stone at the entrance of the historical museum in Amsterdam has been restored in a manner that is less in conflict with the starting points of the restoration. By maintaining the thick layers of paint and only restoring it in some places the stone is still in situ after the restoration a few years ago.